Atrial Strain and Strain Rate: A Novel Method for the Evaluation of Atrial Stunning - Ozkan,Hakan (2016)
Abstract Background: Atrial fibrillation (AF) is the most common arrhythmia seen in adults. Atrial stunning is defined as the temporary mechanical dysfunction of the atrial appendage developing after AF has returned to sinus rhythm (SR). Objectives: We aimed to evaluate atrial contractile functions by strain and strain rate in patients with AF, following pharmacological and electrical cardioversion and to compare it with conventional methods. Methods: This study included 41 patients with persistent AF and 35 age-matched control cases with SR. All the AF patients included in the study had transthoracic and transesophageal echocardiography performed before and after. Septum (SEPsSR), left atrium (LAsSR) and right atrium peak systolic strain rate (RAsSR) were defined as the maximum negative value during atrial contraction and septum (SEPε), left atrium (LAε) and right atrium peak systolic strain (RAε) was defined as the percentage of change. Parameters of two groups were compared. Results: In the AF group, 1st hour and 24th hour LAε, RAε, SEPε, LAsSR, RAsSR, SEPsSR found to be significantly lower than in the control group (LAε: 2.61%±0.13, 3.06%±0.19 vs 6.45%±0.27, p<0.0001; RAε: 4.03%±0.38, 4.50%±0.47 vs 10.12%±0.64, p<0.0001; SEPε: 3.0%±0.22, 3.19%±0.15 vs 6.23%±0.49, p<0.0001; LAsSR: 0.61±0.04s-1, 0.75±0.04s- 1 vs 1.35±0.04s-1, p<0.0001; RAsSR: 1.13±0.06s-1, 1.23±0.07s-1 vs 2.10±0.08s- 1, p<0.0001; SEPsSR: 0.76±0.04s- 1, 0.78±0.04s- 1 vs 1.42±0.06 s- 1, p<0.0001). Conclusion: Atrial strain and strain rate parameters are superior to conventional echocardiographic parameters for the evaluation of atrial stunning in AF cases where SR has been achieved.